A global analysis of the determinants of alien geographical range size in birds. Issue 11 (11th August 2016) - Dyer, Ellie E.; Franks, Victoria; Cassey, Phillip; Collen, Ben; Cope, Robert C.; Jones, Kate E.; Şekercioğlu, Çagan H.; Blackburn, Tim M.
Abstract: Aim Determining the causes of range size variation in the distributions of alien species is important for understanding the spread of invasive species. Factors influencing alien range size have been explored for some species at a regional level, but to date there has been no global analysis of an entire class. Here, we present such an analysis for birds, testing for the effects of introduction event, location and species‐level variables on alien range sizes. Location Global. Methods We used a novel dataset on the global distributions of alien bird species to test for relationships between alien range size and colonization pressure, residence time, extent of the global climatic niche, native range size, body mass and specialization, using a statistical approach based on phylogenetic generalized least squares models. We performed this analysis globally, and for separate biogeographical realms. Results Approximately half of the variation in alien bird range size is explained by colonization pressure in univariate analysis. We identified consistent effects of higher colonization pressure at global and realm levels, as well as support for effects of native range size and residence time. We found less support for effects of body mass, specialization or extent of the global climatic niche on alien range size. Main conclusions Alien bird range sizes are generally small relative to their native range sizes, and many are continuing to expand. Nevertheless, current variation is predictable, most strongly by the event‐level factor of colonization pressure. Whether a species is widespread is a better predictor of alien range size than whether a species could be widespread (estimated by global climatic niche extent), while we also find effects of residence time on alien range size. These relationships may help to identify those alien species that are more likely to spread and hence have greater environmental and economic impacts where they have been introduced.